Branding and Commercialization of Heritage Products and Services Eco-system Framework - Nadianatra, Musa; Dayang Hanani, Abang Ibrahim; Sabariah, Putit; Al-Khalid, Hj Othman; Johari, Abdullah; Noor Alamshah, Bolhassan (The Mattingley Publishing Co., Inc., 2019)
Heritage product or service which is a branch of the invention or tourism package oriented has been identified as significant revenue generation in economy sector in Malaysia. The disappearance of heritage products and traditional services has become increasingly obvious in the tourism industry. This is due to several factors including incapability of connecting and engaging with others lifestyle heritage, cultural and tourism activities, unwillingness of generation to continue intricate craft skills, lack of innovation, creativity and technical skills, lack of compliance in standards or international entry requirements and lack of financial support. Therefore, this paper suggested an ecosystem framework involving thirteen components which reflecting the entrepreneur needs, the government intervention and marketplace platform for sales and marketing. As part of framework development, qualitative and quantitative methods were conducted to examine the components of ecosystem.The collaboration between the academia, the government agencies, cottage entrepreneurs and the industry are essential which would be beneficial for all parties to bring the products and services into sustainable tourism industry.